2007
DOI: 10.1007/s00441-007-0459-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible participation of mitochondria in lipid yolk formation in oocytes of paddlefish and sturgeon

Abstract: The ovary of paddlefish and sturgeons (Acipenseriformes) is composed of discrete units: the ovarian nests and ovarian follicles. The ovarian nests comprise oogonia and numerous early dictyotene oocytes surrounded by somatic prefollicular cells. Each ovarian follicle consists of a spherical oocyte and a layer of follicular cells situated on a thick basal lamina, encompassed by thecal cells. The cytoplasm of previtellogenic oocytes is differentiated into two distinct zones: the homogeneous and granular zones. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…They were present in several ovarian nests in the ovaries of both species. The main difference between EP 1 oocytes described in this study and the early previtellogenic oocytes previously described (identically referred to as the early stage 1 previtellogenic oocytes, Żelazowska & Kilarski, ) was that all oocytes developed in ovarian nests [Fig. (b), (d)] and not within the ovarian follicles.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…They were present in several ovarian nests in the ovaries of both species. The main difference between EP 1 oocytes described in this study and the early previtellogenic oocytes previously described (identically referred to as the early stage 1 previtellogenic oocytes, Żelazowska & Kilarski, ) was that all oocytes developed in ovarian nests [Fig. (b), (d)] and not within the ovarian follicles.…”
Section: Resultsmentioning
confidence: 90%
“…In the ovarian nests of both A. gueldenstaedtii and P. spathula , early previtellogenic oocytes (previously termed the early dictyotene oocytes, Żelazowska & Kilarski, ) were located [Fig. ].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, the mitochondria of L. vannamei become the compartments for the contents of yolk granules through a similar process of phagocytosis. In addition, the research indicated similar transformation of mitochondria participation in yolk formation (Weakley, 1976;Pfannenstiel and Grunig, 1982;Thiaw and Mattei, 1992;Reunov et al, 2000;Zelazowska and Kilarski, 2009). Whether mitochondria, like vitellogenesis, are involved in the formation of cortical granules may require further study apart from TEM technique, however, we suggest that it is possible that some organelles, like mitochondria, take part in the origin of cortical granules.…”
Section: Mitochondria Involvement In the Coalescence Of Miniature Cormentioning
confidence: 87%
“…Yolk formation involves cholesterol uptake and transport mediated by the very low-density lipoprotein receptor on the membrane, and CTSD is the key enzyme in this process [17], [18]. Thus, it has been suggested that CTSD may be a candidate gene associated with egg yolk quality traits.…”
Section: Discussionmentioning
confidence: 99%